Avaliação da atividade e do mecanismo de ação anti-inflamatória de Dilodendron bipinnatum Radlk - Oliveira, Ruberlei Godinho de (2014)
Dilodendron bipinnatum Radlk. (Sapindaceae), popularly known as “mulher-pobre”, is a native tree of the Pantanal of Mato Grosso, Brazil. The inner stem bark of Dilodendron bipinnatum is used by the population, in the forms of decoction and maceration in the treatment of inflammatory conditions. There is no information in the literature demonstrating the anti-inflammatory activity of Dilodendron bipinnatum and its respective mechanism of action. This study aimed to evaluate the anti-inflammatory activity and mechanism of action of the hydroethanolic extract of the stem bark of Dilodendron bipinnatum (HEDb) using in vivo and in vitro experimental models. The stem bark of Dilodendron bipinnatum was macerated in 70% hydroethanolic solution (1:3, w/v) for 7 days, filtered, concentrated on a rotary evaporator and the residual solvent removed in oven at 40 ° C, thus obtaining HEDb. The effect of HEDb on cell viability in murine macrophages (RAW 264.7 cells) was assessed by the Alamar blue assay. The in vivo anti-inflammatory activity and mechanism of action of HEDb (20, 100 and 500 mg/kg) was evaluated in lipopolysaccharide (LPS) -induced peritonitis model in Swiss mice. The peritoneal lavage was collected for the determination of TNF-α, IL-1β and IL-10, using commercial ELISA kits. The in vitro anti-inflammatory studies activity of HEDb (1, 5 and 20 μg/ml) was determined in RAW 264.7 cells stimulated with LPS and/or INF-γ. The supernatant of the stimulated cells was used for the determination of the aforementioned cytokines as well as oxide nitric (NO) by the Griess method. The effect of HEDb on the gene expression of p38 and ERK 1/2 MAPKs and COX-2 was assessed using Western blot assay in RAW 264.7 cells stimulated with LPS. Preliminary phytochemical analysis of HEDb was analyzed by high performance liquid chromatography (HPLC). HEDb showed very low cytotoxicity with IC50>200 ± 0.38 μg/mL. In LPS-induced peritonitis model, HEDb reduced total leukocytes and neutrophils migration, at all doses, reaching maximum effect (45% and 64%, p<0.001 respectively) at 20 mg/kg in both cases. HEDb also attenuated increase in the concentrations of the pro-inflammatory cytokines (IL-1β and TNF-α) and increased level of anti-inflammatory cytokine IL-10 in peritonitis. HEDb had no demonstrable effect on the increased concentrations of TNF-α, IL-10 and NO in activated RAW 264.7 cells. HEDb caused in vitro inhibition of gene expression of MAPK p38 and COX-2. HPLC analyses identified some condensed and hydrolysable tannins, with epigallocatechin gallate being the major compound. HEDb presented a novel multitargeted anti-inflammatory action and mechanism, and low in vitro cytotoxicity. Its anti-inflammatory action was due, at least in part, to the inhibition of cell migration, Th1 type cytokines, expressions of p38 MAPK and COX-2, and to the stimulation of Th2 type cytokine, without affecting NO pathway. It can be suggested that tannins account at least in part to the anti-inflammatory activity of HEDb.